Rahn contract at sharia pawnshop in Madura: analysis of Maqasid al-Shariah, socio-cultural dynamics, and socio-economic impacts - Fauzi, Nur; Humaidi, Humaidi; Ali, Mohammad Mahbubi (LP3M Universitas IslamTribakti Lirboyo Kediri, 2025)
This study examines the implementation of rahn contracts in Islamic pawnshops within the Madurese community, focusing on their alignment with Maqasid al-Shariah principles, the socio-cultural and religious dynamics influencing perception and implementation, and their socio-economic impact. This research is motivated by academic debates regarding the effectiveness of Islamic financial instruments in achieving societal well-being. Using a qualitative approach and a case study method, data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that rahn contracts in Madura’s Islamic pawnshops generally fulfill the objectives of Maqasid al-Shariah, particularly in terms of wealth protection (hifz al-mal) and social welfare. However, implementation still faces challenges, especially regarding transparency and financial literacy among the community. Additionally, cultural and religious dynamics in Madura play a significant role in shaping public perception of rahn, where local wisdom and religious norms influence the utilization of Islamic pawnshop services. From a socio-economic perspective, this study finds that Islamic pawnshops contribute to financial inclusion, providing capital access for small businesses and reducing dependence on interest-based conventional pawn systems. However, challenges remain, such as high administrative fees perceived by some communities and limited access in remote areas. These findings provide crucial insights for developing a more inclusive and community-oriented rahn system. Policy recommendations include enhancing Islamic financial literacy, optimizing rahn-based financing schemes, and strengthening regulations to ensure transparency and sustainability of Islamic pawnshops in Madura